Islamic Boarding School Design - Firmansyah Firmansyah; Wowo Adizar Darwin; Husna Izzati (Jurnal Arsitektur Archicentre, 2022)
The term Islamic Boarding School may be familiar to our ears. The existence of Islamic Boarding Schools has recently mushroomed and has become an attraction for some people. Boarding School is a pre-university level boarding school where all students live in dormitories that have been provided for the duration of their education. We all know that socializing in this millennial era is a scourge for parents, especially for those whose children are in their teens, the presence of the Islamic Boarding School is the answer to these problems, not just a choice but also a need for parents "at the time of now" to send their children to advanced levels. This design carries the concept of tropical architecture, which provides answers/adaptations of building forms to the influence of the tropical climate. The low environment has specific characteristics caused by the sun's heat, high humidity, rainfall, wind movement, and so on. This design is done by looking for literature studies and precedents that will later be used as a reference in designing and analyzing problems, then making comparative studies to create harmony with the function of the building. This design is expected to be a design illustration that can be developed again in the future.